A patient with primary adenocarcinoma of the appendix metastasizing to the ovary - Frgálová, Andrea; Radim, Marek; Klos, Dušan; Hanáček, Jiří; Pilka, Radovan (Ceska gynekologie, 2022)
OBJECTIVE: The aim of this work is to draw attention to the difficulty of differential dia-gnosis of rare adenocarcinoma of the appendix and the histological diversity of ovarian tumors. CASE REPORT: We present a case of a 62-year-old patient sent by an attending gynecologist for the finding of an asymptomatic adnextumor diagnosed during a routine preventive examination. Based on preoperative examinations, a malignant ovarian tumor was suspected. Standard surgery was performed including hysterectomy with bilateral adnexectomy, total omentectomy, appendectomy, pelvic and paraaortic lymphadenectomy. Definitive histopathological analysis revealed a secondary ovarian tumor, with the adenocarcinoma of the appendix appearing to be the primary site. CONCLUSION: Up to 25% of all ovarian tumors are secondary metastatic tumors. Appendix neoplasia should be considered in the differential diagnosis of right-sided adnextumors. Due to their localization, they can only mimic an ovarian tumor during imaging examinations, or they can be the primary origin of an already metastatic ovary, as in our case.
Keywords: Middle Aged; ženské pohlaví; nádory apendixu; apendix; adenokarcinom; Humans; secondary ovarian tumor; nádory vaječníků; Appendiceal Neoplasms; Female; Ovarian Neoplasms; appendiceal adenocarcinoma; Appendix; Adenocarcinoma; lidé; lidé středního věku